Do fragmento à reorganização: movimento estudantil da UFPB (1975-1979) - Nascimento, Talita Hanna cabral (2015)
After the Institutional Act number 5 is decreted, in 1968, it was increasingly difficult to keep an organized movement in Brazil. The student movement, beside other movements like workers' one, was not on the sidelines of the situation: being one of the movements more investigated by the national security organs, the student movement sought to go to other paths, whether in armed struggle or inside the student representative organs, watched over by the military dictatorship: the Central Students Directories. In a politic period of the country known by its "safe, progressive and slow distension", one of the challenges of the Federal University of Paraíba (Universidade Federal da Paraíba, UFPB) student movement was the resumption of its biggest representative entity, the Central Students Directory (Diretório Central dos Estudantes, DCE), from 1976. With the resumption of that space, comes up a whole political and cultural project that not only brought together academic students of UFPB, but also part of the civil society from João Pessoa, to the causes that were beyond students' interests. Therefore, this work addresses the path of reconstruction of the student movement of João Pessoa, aiming to verify the means to the resumption of political-oriented students' activities, as well as student movement's operation and its linking to other civil society sectors. By crossing a theme related to regionality and use of the Politics New History and Politics Culture, this work establish links to this postgraduate program concentration area, namely History and Historic Culture and, more specifically, to the Regional History research area.